Strontium modified calcium phosphate cements - approaches towards targeted stimulation of bone turnover - Schumacher, Matthias; Gelinsky, Michael (Journal of materials chemistry. B, Materials for biology and medicine, 2015)
Making use of the potential of calcium phosphates to host a variety of ions in their crystal lattice, ion substitution of calcium phosphate bone cements has become the subject of intense investigations in the last few years, since this approach allows one to stabilize a bone defect and to locally deliver therapeutic ions into a specific defect site at the same time. In this respect significant attention has been given to strontium ions (Sr 2+ ) lately. Strontium possesses the unique potential to both stimulate new bone formation and inhibit cell-driven bone resorption and thus has been used successfully in systemic osteoporosis therapy. Strontium doping of calcium phosphate bone cements might allow making use of this dual effect to promote local bone defect healing. The goal of this review is to provide an overview of different routes that have been employed to obtain strontium-containing calcium phosphate bone cements and describe their material characteristics as well as their biological properties based on cell culture and animal studies. Strontium modified calcium phosphate cements can target local bone turnover by stimulating osteoblast proliferation and differentiation (1) as well as bone mineralisation (2), reducing osteoclastogenesis (3) and resorption activity, increase osteoclast apoptosis (4) and affect osteoblast/osteoclast paracrine signalling (5).